From the Mediterranean to the southern cone: the transitions to democracy in Chile, Portugal and Spain in a comparative perspective - Feria Vázquez, Pedro (Revista de Historia Social y de las Mentalidades, 2024)
In the present article we will carry out a comparative study of the transitions to democracy that took place in the last quarter of the 20th century in Spain, Portugal and Chile, with the aim of creating an overall vision that helps for a better understanding the political, economic and social evolution of these countries, framing them in their global historical context, and what lessons can be drawn from them. Common factors will be analyzed, such as domestic policy, the economy, the international context, the role of the army and civil society, the incidence of political violence, the negotiation processes between the various political forces and the local peculiarities of each case.
Keywords: Comparative History; Transitions to Democracy; Dictatorships; Political Repression